Community Rice Consumption Level On Small Islands: A Case Study Of Booi And Paperu Villages, Saparua Sub-District, Central Maluku Regency - Clara WT Rantetana; Wardis Girsang; Noviar F. Wenno (Cita konsultindo, 2024)
Food is the most important basic need for humans to live productively. As a staple food, rice is a very important food considering that rice consumption tends to increase along with the increasing population. This research aims to determine the level of rice consumption and the factors that influence rice consumption in Negeri Booi and Paperu, Saparua District, Central Maluku Regency. The research method used a simple random technique by taking 30 household respondents. Data were analyzed using simple tabulation and multiple linear regression analysis. Based on the research results, what can be obtained is that rice consumption is higher compared to local food consumption (sago and tubers) with a total food consumption of rice, sago and sweet potatoes of 0.305 kg/capita/day. This is shown by the value of rice consumption of 0.187 kg/capita/day, sweet potato consumption of 0.116 kg/capita/day and sago consumption of 0.002 kg/capita/day.. The results of the regression test show that the factors that influence the level of rice consumption in Booi and Paperu are sago consumption, income and number of dependents.